Mastering the commodities markets : a step-by-step guide to the markets, products and their trading - Taylor, Francesca (FT mastering series., 2012)
An introduction to commodity markets covering specific commodities such as gold, oil, rare earths, aqua and agriculture. This is a comprehensive introduction to commodities markets, written so that you can quickly scan the book before a meeting and run through the specific chapter that interests you. Designed for the non-specialist, this...